1986
DOI: 10.1073/pnas.83.15.5587
|View full text |Cite
|
Sign up to set email alerts
|

Transfection and homologous recombination involving single-stranded DNA substrates in mammalian cells and nuclear extracts.

Abstract: We have examined the ability of singlestranded DNA to participate in homologous recombination reactions in mammalian cells and nuclear extracts derived from them. We have inserted a fragment of the neo gene into the single-stranded DNA phage vector M13 mphl. The neo fragment was derived from a deletion derivative of the prokaryotic-eukaryotic shuttle vector pSV2neo. The resulting singlestranded DNA was mixed with a double-stranded deletion derivative of pSV2neo and tested for recombination in human cells, monk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 26 publications
6
22
0
Order By: Relevance
“…To determine whether recombination was occurring in COS-1 cells, we cointroduced DL and DR molecules into the cells and calculated the Kanr/Ampr frequency of low-Mw DNA isolated 48 h later. Cotransfection of DL with DR resulted in a 7.5 x 10-frequency of Kanr/Ampr colonies (Table 1), consistent with previous studies (1,33). Because both of the substrate molecules contain deletions within the neo gene, the only way that Kanr colonies may be generated is via a homologous recombination event.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…To determine whether recombination was occurring in COS-1 cells, we cointroduced DL and DR molecules into the cells and calculated the Kanr/Ampr frequency of low-Mw DNA isolated 48 h later. Cotransfection of DL with DR resulted in a 7.5 x 10-frequency of Kanr/Ampr colonies (Table 1), consistent with previous studies (1,33). Because both of the substrate molecules contain deletions within the neo gene, the only way that Kanr colonies may be generated is via a homologous recombination event.…”
Section: Resultssupporting
confidence: 78%
“…Large numbers of extrachromosomal product molecules may be isolated, circumventing some of the difficulties associated with product analysis from nonreplicating systems. Previous studies indicate that recombination between replicating substrates occurs by the same types of mechanisms as in nonreplicating systems (1,33,35). In addition, it has been shown that double-strand breaks, which stimulate recombination in a variety of systems (reviewed in reference 43), are recombinogenic within replicating systems as well (1).…”
mentioning
confidence: 99%
“…Further, we confirmed the differential activity of HR and NHEJ pathways in mESC and fibroblasts by in vitro functional assays [39][40][41]. Recombination reactions using nuclear protein extracts prepared from exponentially growing cells showed a 3-fold increase in HR activity in mESC compared to primary fibroblasts (P value <0.001; Fig.…”
Section: Differential Activity Of Hr and Nhej Repair Pathways In Mescsupporting
confidence: 58%
“…HR catalyzed by cell-free extracts was performed essentially as described previously [39], using a plasmid substrate pair: SalI linearized pSV2neoDL and single-stranded circular ssneoDR, which were kindly provided by Dr. Colin Campbell, University of Minnesota. Briefly, 500 ng of each of these substrates were incubated with nuclear protein extracts prepared from ear fibroblasts or ESC at 378C for 2 h. Purified plasmid DNA was used to electroporate the recombinationdefective Escherichia coli strain DH10B using a Bio-rad Gene Pulser XcellÔ.…”
Section: Cell-free Hr Assaymentioning
confidence: 99%
“…Other studies scrutinized the potential of ssDNA to increase the rate of HR in gene targeting experiments (Rauth et al 1986;Simon & Moore 1987;Baur et al 1990;Bilang et al 1992;Zorin et al 2005) and since single-stranded DNA plays a central role in all proposed recombination models, the use of single-stranded targeting vectors is a promising approach for improving HR. Taken together, most of these experiments demonstrated an increased rate of HR.…”
Section: Different Dna Topologies In Gene Targetingmentioning
confidence: 99%